Abnormal melatonin synthesis in autism spectrum disorders - Melke, Jonas (Nature Publishing Group Specialist Journals, 2008)
Melatonin is produced in the dark by the pineal gland and is a key regulator of circadian and seasonal rhythms. A low melatonin level was reported in individuals with autism spectrum disorders (ASD), but the underlying cause of this deficit was unknown. The ASMT gene, encoding the last enzyme of melatonin synthesis, is located on the pseudo-autosomal region 1 of the sex chromosomes, deleted in several individuals with ASD. In this study, we sequenced all ASMT exons and promoters in individuals with ASD (n=250) and compared the allelic frequencies with controls (n=255). Non-conservative variations of ASMT were identified, including a splicing mutation present in two families with ASD, but not in controls. Two polymorphisms located in the promoter (rs4446909 and rs5989681) were more frequent in ASD compared to controls (P=0.0006) and were associated with a dramatic decrease in ASMT transcripts in blood cell lines (P=2×10(−10)). Biochemical analyses performed on blood platelets and/or cultured cells revealed a highly significant decrease in ASMT activity (P=2×10(−12)) and melatonin level (P=3×10(−11)) in individuals with ASD. These results indicate that a low melatonin level, caused by a primary deficit in ASMT activity, is a risk factor for ASD. They also support ASMT as a susceptibility gene for ASD and highlight the crucial role of melatonin in human cognition and behavior.